Description of Barbutia arasbaraniensis sp. nov. (Acari: Trombidiformes: Barbutiidae) based on the deutonymph and male specimens from Iran - Mojtaba Mohammad Doustaresharaf; Mohammad Bagheri (Persian Journal of Acarology)
A new species, Barbutia arasbaraniensis sp. nov. (Acari: Barbutiidae), is described and illustrated based on deutonymph and male specimens. Also, the key to all known deutonymph species of Barbutia is updated.